Weaning-associated feed deprivation stress causes microbiota disruptions in a novel mucin-containing in vitro model of the piglet colon (MPigut-IVM) - Gresse, Raphaële (J Anim Sci Biotechnol, 2021)
BACKGROUND: Risk factors for the etiology of post-weaning diarrhea, a major problem in swine industry associated with enormous economic losses, remain to be fully elucidated. In concordance with the ethical concerns raised by animal experiments, we developed a new in vitro model of the weaning piglet colon (MPigut-IVM) including a mucin bead compartment to reproduce the mucus surface from the gut to which gut microbes can adhere. RESULTS: Our results indicated that the MPigut-IVM is able to establish a representative piglet archaeal and bacterial colon microbiota in terms of taxonomic composition and function. The MPigut-IVM was consequently used to investigate the potential effects of feed deprivation, a common consequence of weaning in piglets, on the microbiota. The lack of nutrients in the MPigut-IVM led to an increased abundance of Prevotellaceae and Escherichia-Shigella and a decrease in Bacteroidiaceae and confirms previous in vivo findings. On top of a strong increase in redox potential, the feed deprivation stress induced modifications of microbial metabolite production such as a decrease in acetate and an increase in proportional valerate, isovalerate and isobutyrate production. CONCLUSIONS: The MPigut-IVM is able to simulate luminal and mucosal piglet microbiota and represent an innovative tool for comparative studies to investigate the impact of weaning stressors on piglet microbiota. Besides, weaning-associated feed deprivation in piglets provokes disruptions of MPigut-IVM microbiota composition and functionality and could be implicated in the onset of post-weaning dysbiosis in piglets. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40104-021-00584-0.